The impact of corporate governance characteristics on audit report lag : evidence from Malaysian listed companies - Siti Norwahida binti Shukeri (Kulliyyah of Economics & Management Sciences , International Islamic University Malaysia, 2011)
Timeliness of corporate annual financial reports is considered to be a critical and important factor affecting the usefulness of information that is made available to external users. The length of the audit process highly affects the timeliness of corporate financial reporting as documented by prior literature. The purpose of this study is to examine the impact of corporate governance characteristics on audit report lag in Malaysia. The corporate governance characteristics are board independence, audit committee size, audit committee meetings and audit committee qualifications. Consequently, the study applied the agency theory and formulated seven hypotheses that guided the analysis. The study sample comprised 703 Malaysian listed companies from Bursa Malaysia, which complied with the regulatory requirements and subjected to supervision of the Central Bank of Malaysia. Regression analysis was performed to examine the audit report lag determinants. The results show that audit report lag is influenced by audit committee size, auditor type, audit opinion and firm profitability. However, no evidence was found to support the effects of board independence, audit committee meetings and audit committee qualifications on audit report lag. Apart from contributing to the literature on corporate governance and audit timeliness, this study also falls under the strand of literature that examines the consequences of regulatory changes. Detail explanations of the findings of the study along with its implications, limitations and future research suggestions are highlighted.